Opinion 2459: Allodaposuchus precedens Nopcsa, 1928 (Crocodyliformes, Eusuchia, Allodaposuchidae): neotype designated - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has used its plenary power to designate a neotype to replace the non-diagnostic lectotype for the species Allodaposuchus precedens Nopcsa, 1928.
Keywords: Nomenclature; taxonomy; Eusuchia; Allodaposuchidae; Allodaposuchus; Allodaposuchus precedens; Upper Cretaceous; neotype